Four new species and a new record of Synagelides Strand, 1906 (Araneae, Salticidae) from China - Bin-Lu Liu; Xiao-Qi Ning; Shi-Hui Huang; Yan-Bin Yao; Chang-Yong Lin; Jun Yang; Ke-Ke Liu (ZooKeys, 2025)
Four new species of the jumping spider genus Synagelides Strand, 1906 are described from China: S. dajueshan K. K. Liu, sp. nov. (♂, ♀; Jiangxi Province), S. guangfeng K. K. Liu, sp. nov. (♂, ♀; Jiangxi Province), S. kangding K. K. Liu, sp. nov. (♂, ♀; Sichuan Province), and S. wuyuan K. K. Liu, sp. nov. (♂, ♀; Jiangxi Province). Furthermore, S. himalaicus Bohdanowicz, 1987, stat. res. (♂, ♀; Tibet Autonomous Region) is reinstated as a valid species and recorded from China for the first time, with S. jiricus Bohdanowicz, 1987, syn. nov. designated as its junior synonym. All species are comprehensively illustrated with diagnostic photographs and SEM images, and a distribution map is also provided. The geographic distribution of this genus in China and their adaptations are discussed.